Business Digitalization – Cyber Security Concerns - Piotr NIEDZIELSKI; Katarzyna ŁOBACZ; Renata SZANTER (Communications of International Proceedings, 2021)
Digital transformation is paving the pathways for the future, pushing business units to rapid adoption of new digital technologies. But as every change comes with risks, digitalization entails the risk of cyber-attacks, thus the need for ensuring cybersecurity arises. the aim of this paper is to identify the business digitalization risk, by analyzing actions taken by European companies in order to ensure cybersecurity, in relation to threats emerging in the cyber environment. For need of that analysis the authors use data from Eurostat's online database - Community Survey on ICT and e-Commerce Usage in Business - Security Policies: Measures, Risks and Staff Awareness. The analysis of statistical data provides a picture of the progress in ensuring cybersecurity by small, medium and big companies in the 27 EU countries. Conclusions from the analysis can be an inspiration for managers of enterprises on the need to take specific actions in relation to emerging cyber threats.
Keywords: Digitalization; Digital Transformation; ICT Security; Cyber Threats; Security Measures